Participation by Fund Staff In Anti-Money Laundering/Combating The Financing Of Terrorism Assessments by Other Assessor Bodies. (Policy Papers; Policy Paper ;, 2020)
The Fund's Anti-Money Laundering/Combating the Financing of Terrorism (AML/CFT) Strategy was most recently reviewed by the Executive Board in November 2018. In addition, during the Board discussion of the 2018 review, a number of Directors felt strongly that Fund staff should participate in assessments led by other AML/CFT assessor bodies, on an exceptional basis.